The competitive identity of Istanbul: a city brand management model - Levent, Doğan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
Cities have an important place in today's world economy. Due to globalization, many options exist for selecting a city to invest in or visit. As a result, cities continuously compete with each other to be able to increase their gains. The literature indicates that the image is very influential in the process of destination selection. Therefore, the image management is a very crucial task for Istanbul, which is trying to achieve a long term advantageous competitive position among major cities of the world. The main objective of this study is suggesting a brand management model for Istanbul based on evaluation of attributes stressed in the formal communication of Istanbul in the light of the views of visitors. For this purpose, a content analysis was done on the communication materials used in European countries and a survey was conducted with 274 Europeans, who have been to Istanbul. For the statistical analysis of data, frequency, t-test, one-way ANOVA and the factor analyses were employed. Attitude-Toward-Object Model of Fishbein (1967) was used for overall attitude evaluation and the Competitive Identity Model of Anholt (2007) provided the basis for strategy formulation. The findings reveal that Istanbul‟s image among European visitors is generally positive and the communication of Istanbul for European countries highlights proper attributes. However, it is detected that some areas necessitate progress. In the light of the findings, some ideas were developed and a management structure was proposed for maintaining the positive image of Istanbul among visitors and carrying it to the upper league in the competition of cities.
Keywords: Place marketing.; Product management.